End games, time inconsistency and European economic and monetary union - Clark, Alexandra Jane (School of Economics, 2023)
The vision of a monetary union in Europe is as old as the European Community itself, and yet despite the vast amounts of time, effort and political capital spent to build such a system, little progress has to date been made. Most recently, the Maastricht Treaty has set out a strategy and a timetable for monetary union in the Community. One can only ask if there is the likelihood that the process be once more obstructed and if so what the causes might be. This paper, presented in the form of a descriptive analysis of the issues, was motivated by this line of thought. Clearly, there would be endless adjustment difficulties involved in the transitionary process: most have been well documented. To date though, the consequences of the uncontrollable behaviour of rational economic agents within the context of this situation has been left largely unchallenged. The aim of this paper is to attempt to shed light on this issue. The analysis described is within a simple game theoretic framework. When it is declared that monetary union is to be formed. the various games begin. Unlike before, rational agents - or the players in the game - now face finite time horizons. They engage in activities that enable them to exploit the incentives that have become available to them under these conditions. These end game activities have detrimental effects on the old and new regimes and invariably render the plan (proposed monetary union) time inconsistent. And they, clearly are inevitable: rational agents will always seek to maximise their welfare no matter what the circumstances are. As such and depending of course on the type of end game played. monetary union in its transitionary phases will always be in danger of being derailed. All that the policy makers and negotiators can do is to seek ways of minimising these activities. While strongly endorsing the convergence criteria and the penalties for any intentional deviating activity, every attempt should be made by these bodies to build up a credible reputation for the transitionary process and institutional set up once the monetary union has been established. If the monetary union is deemed credible, i.e. the players perceive it to be a worthwhile goal, then rational agents will seek to avoid engaging themselves in these activities.